Pengembangan Buku Cerita Bergambar pada Mata Pelajaran IPA Terpadu Materi Klasifikasi Makhluk Hidup bagi Siswa SMP Kelas VII - Dua Rina, Veronika; Yoseph Tuta Mago, Oktavius; Hadi Jaya Putra, Sukarman (Universitas Cokroaminoto Palopo, 2024)
A picture story book is a book that contains a story and is accompanied by pictures or illustrations to support the content of the story. Based on the results of the observations made, the researcher found several problems experienced by students, namely, lack of learning media and lack of reading literacy. With the problems found by the researcher, they developed learning media in the form of picture story books with the title of classification of living things using the 4D method, namely Devine (Definition), Design (Design), Develop (development) and Disseminate (disseminate). The purpose of developing this picture story book product is as a learning material. The stages of product validation use questionnaires, assessments for validator experts, namely material validation tests, media validation and language validation. The subject of this study is a student of grade VII of SMP Negeri 1 Talibura. The results of this study show that the resulting product is very valid for use by obtaining presentations by 88.75% material validation, 100% media validation and 96.6% language validation. Meanwhile, the results of the assessment of the feasibility of picture story books by teachers were 96%, and students were 93.56%. The picture story book developed in this assessment proved to be very valid and worthy of use.